First discovery of gibbsite in Biryuzakan turquoise deposit, Northern Tajikistan - Sh. T. Vosihov; A. K. Litvinenko; M. A. Rassomakhin (Известия высших учебных заведений: Геология и разведка)
Background. In the quartz veins of the Biryuzakan turquoise deposit, a hydrothermal mineralization of varicolored gibbsite was discovered for the first time. The gibbsite varies from light- to dark blue in color, resembling turquoise. Aim. To conduct a mineralogical study of the gibbsite contained the Biryuzakan vein turquoise deposit. Materials and methods. Stone samples from the Biryuzakan turquoise deposit (northern part of the  Republic of Tajikistan), where gibbsite had been found, were collected during fieldworks in 2023. The samples were studied using (1) X-ray phase analysis by a DRON-4-07 diffractometer, with a Cu-anode and a Ni-filter, U — 35 kV, I — 20 mA, imaging speed — 1 deg/min, internal standard — quartz (analyst M. Saimudasiri, Sergo Ordzhonikidze Russian State University for Geological Prospecting) and (2) X-ray microanalysis by a Tescan VEGA 3sbu scanning electron microscope equipped with an Oxford Instruments X-act energy dispersive spectrometer (EDS). The analytical conditions were as follows: accelerating voltage — 20 kV, beam current — 20 nA, spectrum acquisition time — 120 s, Certified Standard No. 1362 (Microanalysis Consultants Ltd), MINM25-53  (Astimes Scientific Limited, serial number 01-044) etalons. Results. In the composition of vein formations of the Biryuzakan deposit, we established the presence of gibbsite — aluminum hydroxide — and studied its phase and chemical compositions. The gibbsite veins of Biryuzakan and, possibly, of the Burgundy gold deposit can be attributed to the alunite formation of low-temperature hydrothermal veins. Conclusion. The bright blue gibbsite of Biryuzakan might have been encountered previously bygeologists investigating the deposit for the presence of turquoise. When examining blue samples, turquoise inserts might be misdiagnosed, since blue gibbsite can be visually confused with highgrade turquoise. Our discovery of gibbsite extends the spectrum of mineral associations of the geological object under study and sets the task of inspecting the turquoise mined earlier and products therefrom. The discovered gibbsite is characterized by a complex isomorphism: more than 17% of impurities, including copper, manganese and fluorine (about 5%).